A modified damage-coupled viscoplastic constitutive model for capturing the asymmetric behavior of a nickel-based superalloy under wide creep-fatigue loadings. (November 2022) - Sun, Li; Liu, Li-Qiang; Wang, Run-Zi; Wang, Xiao-Wei; Tan, Jian-Ping; Guo, Su-Juan; Wang, Ji; Zhang, Ding-Wu; Zhang, Xian-Cheng; Tu, Shan-Tung
Highlights: Asymmetric cyclic softening is analyzed under wide creep-fatigue loadings. Back stress is dominant and isotropic stress is secondary in cyclic deformation. A modified viscoplastic constitutive model is established to describe deformation. A damage variable coupled into model is validated via life prediction. Abstract: In this study, cyclic deformation behaviors of nickel-based GH4169 superalloy are investigated in both experimental and simulated aspects via cyclic loading waveforms (i.e., PP, CP, PC and CC) at 650℃. Cyclic softening, stress relaxation and damage evolutions are analyzed, in which asymmetric cyclic softening in both peak/valley directions are demonstrated. The analysis of internal stress evolutions indicates that back stress is dominant and isotropic stress is secondary in cyclic softening. Afterward, a modified damage-coupled viscoplastic constitutive model is established to describe the complex cyclic behaviors as well as the damage evolutions. A term related to the first invariant of stress is incorporated into isotropic hardening rule and a softening factor introduced into the Ohno-Wang kinematic hardening rule. Additionally, a damage variable related to Young's modulus is coupled into the model, which is experimentally validated via life prediction for more abundant experimental data points. The modified model is expected to provide an in-depth insight into cyclic behaviors and fatigue life under wide loading waveforms for industrial applications.